At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
x = 7
Step-by-step explanation:
3(2x + 4) - x = 47
Multiply out the brackets: 6x + 12 - x = 47
Collect like terms: 6x - x + 12 = 47
Combine like terms: 5x + 12 = 47
Subtract 12 from both sides: 5x = 35
Divide both sides by 5: x = 7
Step-by-step explanation:
Open the bracket by using the number outside the bracket to multiply the ones inside.
Opening the bracket, we have that; 6x+12 - x =47
6x-x+12=47
5x+12=47
Collect like terms,
5x=47-12
5x=35
d.b.s by 5 to make x the subject
5x/5=35/5
x=7
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.